2015
DOI: 10.2147/oajsm.s74622
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a tailored neck training program on neck strength, movement, and fatigue in under-19 male rugby players: a randomized controlled pilot study

Abstract: PurposeTo investigate the effect of a tailored neck muscle conditioning program on neck muscle strength, neck muscle fatigue, and range of neck movement in 16–18-year-old male rugby players.Materials and methodsThirty-four male rugby players were divided into forward and back playing positions and randomized within these groups. Seventeen players were randomly assigned to each group. The test group was given a tailored 6-week exercise regime based on their baseline measurements to be performed three times a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…During the literature search of this review, no prospective trials were identified that evaluated training protocols for concussion prevention. As head acceleration plays a role in the pathophysiology of concussions, prevention strategies involving the development of a strong and massive neck musculature have been proposed 82 83. In a study of high school soccer, basketball and lacrosse athletes, overall neck strength, a measure of combined strength in flexion, extension and lateral flexion, and neck circumference were lesser in athletes who sustained concussions in comparison to their uninjured peers 82.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the literature search of this review, no prospective trials were identified that evaluated training protocols for concussion prevention. As head acceleration plays a role in the pathophysiology of concussions, prevention strategies involving the development of a strong and massive neck musculature have been proposed 82 83. In a study of high school soccer, basketball and lacrosse athletes, overall neck strength, a measure of combined strength in flexion, extension and lateral flexion, and neck circumference were lesser in athletes who sustained concussions in comparison to their uninjured peers 82.…”
Section: Discussionmentioning
confidence: 99%
“…Isometric neck flexion and extension strength as well as neck girth can be increased significantly in just 8 weeks of training 84. Recently, investigators reported trends towards increased neck strength in rugby players after only 6 weeks of training 83. In addition, pilot results from an intervention that included a 5 min tackling drill without helmets and shoulder pads reduced head impacts in collegiate football players over a single competitive season 85.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effect of different neck-strengthening programs with varying results. Strengthening programs that involved 50% to 70% maximal voluntary contraction during exercises for 5 to 6 weeks resulted in no clinically meaningful changes in total neck strength in male rugby players 2 under 19 years old or professional rugby players. 24 A 5-week program involving maximal resistance to an external load applied by a strength and conditioning coach resulted in a clinically significant ~19% increase in total neck strength compared with baseline in professional rugby players.…”
Section: Discussionmentioning
confidence: 93%
“…1,19 To be effective as an injury prevention measure in the real world, 12 players must comply with the injury-prevention program. 22 Two neck-strengthening programs required equipment such as weights machines 2,24 or head harnesses 18,24 and required ~8 15 to 20 minutes 2 per player to perform, and 1 required trained personnel such as strength and conditioning coaches to apply resistance. 15 Time, personnel, and equipment are common barriers to compliance, particularly within nonprofessional settings.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the 'break' test is to use the 'make' test, which is performed using a head harness attached to a load cell device to a fixed frame or tested against a manual resistance in seated or lying positions with the participant exerting maximal strength against the load cell or handheld dynamometer [7,19,20]. The reliability of make test isometric neck strength measures from a load cell in healthy individuals was excellent between-day (ICC 0.94-0.98) performed in sitting position [21].…”
Section: Introductionmentioning
confidence: 99%